Hollow Li/Al-LDH architecture engineering to accelerate mass transfer for high-efficiency low-grade lithium extraction - Chenghao Qiu; Yujiao Cao; Haiping Su; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

EPS-Mediated Sludge Dewatering: Molecular Structure and Interfacial Behavior - Haiping Yuan; Lin Gu; Xiao Cao; Nanwen Zhu (Bioresource Technology, 2026)

Oxygen-driven shift from Pb(II) lattice incorporation to reversible surface complexation: Exploiting hydrothermal sludge DOM for high-purity vivianite recovery - Xin Wang; Chaoyue Tai; Lexuan Wang; Yuanyuan Pei; Zhehao Li; Yiyang He; Suyun Xu; Lin Gu; Hanlin Zhang; Haiping Yuan; Haifeng Wen (Water Research, 2026)

Predictors, sources, and health risks of environmental antibiotic exposure in Chinese pregnant women - Lu Qian; Yi Wang; Sumiao Hong; Yuanping Wang; Haiping Lin; Yuanyuan Chen; Baochang Sun; Yu Liu; Mingxue Wang; Xinyi Zhu; Haozhe Gu; Jiaqi Liu; et al. (Environmental Pollution, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Intelligent recognition of the fermentation stage of baijiu based on multi-dimensional data fusion and interpretable machine learning - Lin Du; Junchao Zhou; Yongqing Tang; Xuan Liu; Jing Zhong; Bo Yang; Yuancheng He; Xianguo Tuo; Haiping Du (Food Research International, 2026)

Multi-omics analysis investigates the effects of replacing fishmeal with intestinal mucosal protein on growth performance and intestinal health in hybrid sturgeon - Yuanfa He; Jun Wen; Hang Chen; Guangjun Lv; Yongjun Chen; Shimei Lin; Haiping Liu; Zhijian Wang; Hailong Ge (Aquaculture, 2026)

Discrepancies in microbial nitrogen cycling among diverse karst hydrological systems: enhanced nitrate reduction potential in karst conduits - Danni Zhu; Yi Li; Lihua Niu; Changsong Zhou; Lianjie Fan; Haiping Lu; Li Lin (CATENA, 2026)

The role of forest mushroom systems in soil fungal community reorganization and carbon fractions - Zihao Ye; Xudan Zhu; Yuyou Zhi; Haiping Lin; Jiasen Wu (Agriculture, Ecosystems & Environment, 2026)

Dual-Path valorization of organic waste via black soldier fly: Synergistic enhancement of feed efficiency, crop quality, and climate mitigation in closed-loop aquaculture - Longjun Chen; Yu Lin; Xianbo Jia; Xiangzhou Zheng; Yuchen Zhuo; QianQian Chen; Haiping Fan; Yu Fang; Hui Zhang; Chenqiang Lin (Waste Management, 2026)

Glacial changes in the eastern Kunlun Mountains since the Little Ice Age - Sai Lin; Jinhua Liu; Yingkui Li; Haiping Hu; Changsheng Ye; Qiang Liu; Shunzi Pi (Quaternary International, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Exposure to triclosan and triclocarban is associated with estrogen metabolism in Chinese pregnant women - Min Huang; Yi Wang; Yuanping Wang; Baochang Sun; Guankai Lin; Ke Zhao; Jiaqi Liu; You Zhou; Xiaoting Wen; Xiaoyang Xu; Sumiao Hong; Yuanyuan Chen; et al. (Environmental Research, 2026)

Photosensitized degradation of tetracycline by extracellular polymeric substances (EPS) in biochemical effluent: Mechanistic insights from spectroscopy - Xiao Cao; Xinchao Zhang; Yiyang He; Suyun Xu; Songrui Yang; Haiping Yuan; Shifei Kang; Lin Gu (Journal of Environmental Chemical Engineering, 2025)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Biogenic synthesis of selenium nanoparticles by Bacillus amyloliquefaciens: A promising method for mitigating mycotoxin contamination and fighting Fusarium graminearum - Ezzeldin Ibrahim; Yan Fang; Raghda Nasser; Dan Wang; Doaa Abd El-maksoud Khalil Kafsheer; Solabomi Olaitan Ayoade; Rahila Hafeez; Wafa Abdullah I. Al-Megrin; Bin Li; Haiping Lin (Journal of Hazardous Materials, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Development of cyclic double virtual phase model for advanced packed bed solar-driven thermo-chemical reactor - Hongyang Zuo; Qingyang Zhang; Kuo Zeng; Meng Lin; Ange Nzihou; Haiping Yang; Hanping Chen (Chemical Engineering Journal, 2025)

Natural bio-photosensitizers in sludge: Extracellular polymeric substances (EPS)-driven persulfate activation for sustainable antibiotic degradation - Yiyang He; Hanlin Zhang; Xinchao Zhang; Yuanyuan Pei; Xin Wang; Xiao Cao; Haiping Yuan; Xi Xiong; Lin Gu; Songrui Yang (Journal of Cleaner Production, 2025)

Corrigendum to “Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils” [Biomass & Bioenergy 197 (2025) 107823] - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

The enhancement of extracellular electron transfer processes through the design of biomimetic grape-like materials - Yao Meng; Xu Pan; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang (Journal of Environmental Chemical Engineering, 2025)

Synergistic effect of bimetallic bioelectrocatalysis and endogenous soluble electron mediators for functional regulation of electroactive biofilms - Xu Pan; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang (Journal of Cleaner Production, 2025)

Boosting lactic acid photocatalytic synthesis from biomass sugars: The synergistic effect of N-doped carbon dots on ultrathin carbon nitride - Xiao Cao; Xin Wang; Yiyang He; Jixin Li; Haiyan Yang; Pingping Zhang; Songrui Yang; Haixiang Yu; Suyun Xu; Haiping Yuan; Lin Gu (Food Chemistry, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Efficient hydrogen production from food waste leachate using single-chamber microbial electrolysis cell - Shuyue Ma; Yifan Zhang; Lingli Tu; Xin Li; Xindi Chen; Songwei Lin; Haiping Luo; Xinmin Zhan; Guangli Liu (Environmental Research, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Insight into simultaneously sludge dewatering and antiviral drugs removal by integrated particle electrodes assisted electrochemical oxidation - Haixiang Yu; Yiyang He; Hong Tao; Haiping Yuan; Feiyan Wu; Rusen Zou; Suyun Xu; Lin Gu (Journal of Environmental Chemical Engineering, 2024)

Uncovering and preventing polytellurides dissolution enables stable sodium-ion storage: A case study of SnTe - Zhixin Liang; Jianlian Huang; Wei Zhang; Heying Chu; Qinghua Li; Haibin Lu; Zeyu Lin; Junling Wang; Haiping Lin; Yuyang Chen; Shiyun Xiong; Shaoming Huang (Chemical Engineering Journal, 2024)

Enhancing lithium extraction from low grade salt lake brines using high powder loading aluminum-based adsorbent granules - Yanan Pan; Ye Zhang; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2024)

Advanced application of tea residue extracts rich in polyphenols for enhancing sludge dewaterability: Unraveling the role of pH regulation - Haixiang Yu; Xin Wang; Ya Chen; Yiyang He; Siting Yang; Haiping Yuan; Hong Tao; Suyun Xu; Lin Gu (Environmental Research, 2024)

Resource utilization of coal chemical waste salt by bipolar membrane electrodialysis with thermal pretreatment - Haoran Xin; Xindi Chen; Songwei Lin; Haiping Luo; Yingjie Cao; Chuyang Y. Tang; Guangli Liu (Desalination, 2024)

Cross-linked Polypyrrole@Co3O4 for boosting bioenergy output and regulating electroactive microflora in sediment microbial fuel cells - Xuanyi Zhu; Kangnan Liu; Zhenghui Qiu; Qing Wen; Cunguo Lin; Haiping Gao; Jiaxuan Liu; Shaochuan Wang (Journal of Environmental Chemical Engineering, 2024)

Design and synthesis of a new bioactive compound for marine antifouling inspired by natural products - Jiyong Zheng; Haiping Gao; Guanglong Zhang; Zhiyong Sun; Jinwei Zhang; Li Wang; Cunguo Lin (Natural Product Research, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

Bimetallic ZIF-derived heteroatomic-doped bioanode catalysts for enhanced power production in microbial fuel cells - Liuqingying Yang; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qi; Xu Pan (Fuel, 2024)

Desorption enhancement of aluminum-based adsorbent in lithium extraction from sulfate-type salt lakes - Yihong Guo; Jianguo Yu; Haiping Su; Sen Lin (Desalination, 2024)

Rational construction Ag/LiF/sulfide rich protective layer for remarkably enhancing the stability of Li metal anodes - Caili Xu; Shu Zhang; Cheng Chen; Yunhui Lin; Bing Qu; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2024)

Electrostatic self-assembled nickel cobalt sulfide/Ti3C2 Mxene as a bio-capacitive anode for specific attracting sulfur-cycling bacteria and regulating extracellular electron transfer efficiency - Haitao Xu; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang; Xu Pan (Journal of Cleaner Production, 2024)

Sustainable in situ ammonia recovery from municipal solid waste leachate in a single-stream microbial desalination cell - Yaobin Lu; Dong Lin; Guangli Liu; Haiping Luo; Renduo Zhang; Tiangang Luan (Journal of Environmental Management, 2024)

Abandonment of Moso Bamboo (Phyllostachys pubescens) Plantations Could Lead to Stand Structural Complications and Changes in Soil Properties and Microbial Community - Jin Jin; Liuxin Ye; Zeng Wang; Weijun Fu; Haiping Lin; Jiasen Wu (Journal of Soil Science and Plant Nutrition, 2023)

Lithium extraction process from low grade Na+/K+ brines dependent on high layer charge layered double hydroxides - Bingchun Sheng; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2023)

Nitrogen-doped carbon coated zinc as powder-based anode with PVA-gel electrolyte enhancing cycling performance for zinc-ion batteries - Yunhui Lin; Ming Zhang; Youzuo Hu; Shu Zhang; Ziqiang Xu; Tingting Feng; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2023)

The role of binary transition metal Cobalt-Nickel sulfide as an anode catalyst in specifically selection of Desulfuromonas and improved performance of microbial fuel cell - Haitao Xu; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang; Xu Pan (Chemical Engineering Journal, 2023)

Spatial stratification of cathodic biofilm on nitrogen removal in the microbial fuel cell under different carbon/nitrogen ratios - Jieling Li; Songwei Lin; Ting Wang; Haiping Luo; Guangli Liu; Renduo Zhang (Journal of Water Process Engineering, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Sulfate removal from the seawater using single-chamber bioelectrochemical system - Jing Huang; Cuiping Zeng; Haiping Luo; Songwei Lin; Guangli Liu; Renduo Zhang (Desalination, 2023)

A super PPR cluster for restoring fertility revealed by genetic mapping, homocap-seq and de novo assembly in cotton - Bin Gao; Gaofeng Ren; Tianwang Wen; Haiping Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

A new buffer selection strategy for land use regression model of PM2.5 in Xi’an, China - Zeyu Liu; Qingyu Guan; Jinkuo Lin; Liqin Yang; Haiping Luo; Ning Wang (Environmental Science and Pollution Research, 2021)

Influence of high-dose continuous applications of pyroligneous acids on soil health assessed based on pH, moisture content and three hydrolases - Huidong Maliang; Linghan Tang; Haiping Lin; Anliang Chen; Jianyi Ma (Environmental Science and Pollution Research, 2020)

Abundance and residency dynamics of the Indo‐Pacific humpback dolphin, Sousa chinensis , in the Dafengjiang River Estuary, China - Chongwei Peng; Haiping Wu; Xianyan Wang; Qian Zhu; Thomas A. Jefferson; Chun‐Chieh Wang; Youhou Xu; Jian Li; Hu Huang; Mo Chen; Shiang‐Lin Huang (Marine Mammal Science, 2020)
Robust population size estimates are essential for informing population conservation status. Residency dynamics show population habitat use through time. Population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) has been extensively investigated in Chinese waters, but their residency dynamics are rarely known. Mark‐recapture analysis based on photo‐identification records was applied to humpback dolphins in the Dafengjiang River Estuary habitat, one of the key habitats in the northern Beibu Gulf, China. Movement analyses based on lagged identification rate indicated the humpback dolphins spent, on average, 78.5 days inside and 46.9 days outside the survey area. Within the study area, the humpback dolphin abundance was 83 identifiable dolphins. A total of 353–430 humpback dolphins, estimated by POPAN modeling, were involved in this fluid habitat‐use dynamic. Robust Design analysis showed strong seasonality in humpback dolphin abundance and emigration probability, implying a movement‐ and habitat‐use pattern likely associated with spatiotemporal distribution of oceanographic characteristics and prey occurrences. Population surveys and conservation measures currently conducted in Chinese waters seldom consider seasonality in movements between habitat patches, which can be addressed by genetic analyses across habitats and cross‐matching photo‐identification records among neighboring habitats.

Dolphin-watching tourism and indo-Pacific humpback dolphins (Sousa chinensis) in Sanniang Bay, China: impacts and solutions - Haiping Wu; Chongwei Peng; Hu Huang; Thomas A. Jefferson; Shiang-Lin Huang; Mo Chen; Qianhui Zeng; Xueying Yu; Xianyan Wang; Youhou Xu (European Journal of Wildlife Research, 2020)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

The microbiomic and environmental analysis of sediments in the Indo-Pacific humpback dolphin (Sousa chinensis) habitat in the Northern Beibu Gulf, China - Bin Gong; Hu Huang; Chongwei Peng; Jingzhen Wang; Jixian Ma; Xiangxu Liu; Songying Ouyang; Shiang-Lin Huang; Haiping Wu (Environmental Science and Pollution Research, 2019)

Identification of Novel SCIRR69-Interacting Proteins During ER Stress Using SILAC-Immunoprecipitation Quantitative Proteomics Approach - Yujian Chen; Yong Liu; Shide Lin; Shuguang Yang; Haiping Que; Shaojun Liu (NeuroMolecular Medicine, 2017)

Genome expression profile analysis of the maize sheath in response to inoculation to R. solani - Jian Gao; Zhe Chen; Mao Luo; Hua Peng; Haijian Lin; Cheng Qin; Guangsheng Yuan; Yaou Shen; Haiping Ding; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Molecular Biology Reports, 2014)

Enhanced adsorptive removal of naphthalene intermediates from aqueous solution by introducing reed straw into sewage sludge-based activated carbon - Lin Gu; Huaqing Guo; Pin Zhou; Nanwen Zhu; Daofang Zhang; Haiping Yuan; Ziyang Lou (Environmental Science and Pollution Research, 2014)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Binding of triclosan to human serum albumin: insight into the molecular toxicity of emerging contaminant - Jiabin Chen; Xuefei Zhou; Yalei Zhang; Yanqin Zi; Yajie Qian; Haiping Gao; Shuangshuang Lin (Environmental Science and Pollution Research, 2012)